274 Tumoral and peripheral immunophenotype of refractory vs relapse to PD-(L)1 blockade in patients with advanced non-small cell lung cancer. (10th December 2020) - Ascierto, Maria; Hellmann, Matthew; Standifer, Nathan; Wu, Song; Si, Han; Morehouse, Chris; Rebelatto, Marlon; Abdullah, Shaad; Raja, Rajiv; Soria, Jean-Charles; Germa, Caroline; Barrett, Carl
Abstract : Background: Despite the encouraging successes of immune checkpoint inhibitors, many patients do not benefit and are either refractory or relapse. The mechanisms of refractory or relapsed disease following PD-(L)1 blockade are largely unknown. To identify characteristics associated with refractory or relapsed disease we explored the immune and genomic landscape of samples derived from NSCLC patients who previously received PD-(L)1 blockade and had blood and fresh tumor biopsies collected at the time of progression. Methods: Patient response categories were defined prospectively; 'refractory' defined as progression within 16 weeks of initiating PD-(L)1 and 'relapse' defined as initial clinical benefit (CR, PR, SD) followed by progression. RNAseq (n=52) and PD-L1 IHC (n=22) were performed on tumor tissue. Immune profiling of whole blood was assessed using flow cytometry or Biomark HD (Fluidigm) gene expression panel (n=54 and n=62, respectively). Differential gene expression was defined as unadjusted p<0.05 and fold-difference >1.5. Pathways analysis was conducted by David tool. Patient samples were collected during screening for clinical trial of second line immunotherapy. Written informed consent was obtained from the patients for publication of this abstract. Results: In patients with NSCLC previously treated with PD-(L)1 blockade, tumors of relapsed patients were characterized by increased expression of genes associated with interferon signaling (e.g. CXCL9, SPIC, IFNg), immune suppression (e.g. ARG1, TGFB), immune exhaustion (e.g. ADORA2A), and increased PD-L1 expression (by gene expression and IHC). Refractory disease was associated with increased cadherin signaling and calcium-dependent-cell-adhesion gene expression pathways. In the periphery, reduced quantities of B cells and activated (HLA-DR+ or CD38+) or proliferating (Ki67+) CD8+ T cells were observed in refractory patients. Conclusions: The tumor and peripheral compartments of patients with NSCLC previously treated with PD-(L)1 blockade differ based on prior response. Relapsed patients tend to have signals of sturdy immune activation and chronic inflammation thus ultimately leading to immune exhaustion. These results may help inform rational therapeutic strategies to overcome resistance to PD-(L)1 blockade in NSCLC. Trial Registration: NCT02000947 Ethics Approval: Research on human samples here analyzed have been performed in accordance with the Declaration of Helsinki. Consent: Written informed consent was obtained from the patient for publication of this abstract.